2008
DOI: 10.1364/oe.16.018992
|View full text |Cite
|
Sign up to set email alerts
|

All-optical half adder based on cross structures in two-dimensional photonic crystals

Abstract: We propose an all-optical half adder based on two different cross structures in two-dimensional photonic crystals. One cross structure contains nonlinear materials and functions as an "AND" logic gate. The other one only contains linear materials and acts as an "XOR" logic gate. The system is demonstrated numerically by the FDTD method to work as expected. The optimal operating speed without considering the response time of the nonlinear material, the least ON to OFF logic-level contrast ratio, and the minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(40 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…It is shown that in order to reduce the computational process, the slab structure can be modeled by a 2D structure of infinite height with an effective index [10][11], [14], [20][21][22][23][24][25]. In [21] a detailed study regarding the replacement of 3D analysis with 2D analysis has been made.…”
Section: Numerical Discussionmentioning
confidence: 99%
“…It is shown that in order to reduce the computational process, the slab structure can be modeled by a 2D structure of infinite height with an effective index [10][11], [14], [20][21][22][23][24][25]. In [21] a detailed study regarding the replacement of 3D analysis with 2D analysis has been made.…”
Section: Numerical Discussionmentioning
confidence: 99%
“…However, the large size of the bulk ferromagnetic and lithium niobate crystals, of the order of several millimeters, is unsuitable for practical chip-integrated applications [10,11]. Various schemes have been proposed to demonstrate all-optical basic logic gates based on linear interference mechanisms (or thirdorder nonlinear optical effects) in photonic microstructures and plasmonic nanostructures, such as photonic crystals [12][13][14][15][16][17][18][19][20][21][22][23], microring resonators [24][25][26][27][28][29][30], nanobridges [31], graphene-oxide films [32,33], photonic and plasmonic nanowires [34][35][36], metamaterials [37][38][39], and semiconductor optical amplifiers [40,41]. The extremely high requirements placed on the light paths for the linear interference mechanism and relatively small third-order nonlinear susceptibility of conventional materials result in a low output logic state contrast of <10 dB and high signal intensities of several GW/cm 2 for basic all-optical logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used all-optical schemes for implementation of adder are All optical integrated full adder-subtractor and demultiplexer using SOA-based Mach-Zehnder interferometer [2], photonic crystals [3], dark/ bright solitons [4],quantum dot SOA based MZI [5] In this paper a simple novel all-optical full adder is simulated at 100Gb/s by employing the XGM(Cross Gain Modulation) in semiconductor optical amplifier This circuit uses dispersion managed soliton pulses as input signal and it can be used opamp circuits, adaptive filter implementation, processors, arithmetic circuits etc.…”
Section: Introductionmentioning
confidence: 99%